A Survival Association Study of 102 Polymorphisms Previously Associated with Survival Outcomes in Colorectal Cancer. (12th May 2015) - Savas, Sevtap; Xu, Jingxiong; Werdyani, Salem; Shestopaloff, Konstantin; Dicks, Elizabeth; Green, Jane; Parfrey, Patrick; Green, Roger; Xu, Wei
Abstract : Several published studies identified associations of a number of polymorphisms with a variety of survival outcomes in colorectal cancer. In this study, we aimed to explore 102 previously reported common genetic polymorphisms and their associations with overall survival (OS) and disease-free survival (DFS) in a colorectal cancer patient cohort from Newfoundland n = 505 . Genotypes were obtained using a genomewide SNP genotyping platform. For each polymorphism, the best possible genetic model was estimated for both overall survival and disease-free survival using a previously published approach. These SNPs were then analyzed under their genetic models by Cox regression method. Correction for multiple comparisons was performed by the False Discovery Rate (FDR) method. Univariate analysis results showed that RRM1 -rs12806698, IFNGR1 -rs1327474, DDX20 -rs197412, and PTGS2 -rs5275 polymorphisms were nominally associated with OS or DFS p < 0.01 . In stage-adjusted analysis, the nominal associations of DDX20 -rs197412, PTGS2 -rs5275, and HSPA5 -rs391957 with DFS were detected. However, after FDR correction none of these polymorphisms remained significantly associated with the survival outcomes. We conclude that polymorphisms investigated in this study are not associated with OS or DFS in our colorectal cancer patient cohort.